PERSEPSI PENGELOLA DAN KARYAWAN HOTEL TERHADAP ADOPSI INOVASI PROGRAM SAPTA PESONA: KASUS HOTEL DI JAKARTA TIMUR - Roy Daniel Samboh (Panorama Nusantara, 2016)
Sapta Pesona is a program to increase community awareness, responsibility and action in supporting tourism activity to its development. Jakarta as a capital city of Indonesia and as a tourism destination with all the potentialities they have, include of hotel. The perception of hoteliers and employment to sapta pesona program then become an important point to be analized due to its adoption to develop tourism sector especially in east Jakarta.The study could be summarized as follows: their perception and adoption are sufficiently state level. to increase perception and adoption can be conducted by improving training, and activity such as workshop related to hotel and tourism.